Scheduling with optimized communication for time-triggered embedded systems - Pop, Paul; Eles, Petru; Peng, Zebo (Hardware/Software Codesign 1999: Proceedings of the IEEE 7th International Conference, 1999)
We present an approach to process scheduling for synthesis of safety-critical distributed embedded systems. Our system model captures both the flow of data and that of control. The communication model is based on a time-triggered protocol. We take into consideration overheads due to communication and the execution environment. Communications have been optimized through packaging of messages into slots with a properly selected order and lengths. Several experiments demonstrate the efficiency of the approach.